ESTIMATION OF TOTAL PHENOL AND ANTIOXIDANT ACTIVITY OF ZANTHOXYLUM ARMATUM OF NEPALESE ORIGIN - DHAKAL, DURGA; SHARMA, KHAGA RAJ (International Journal of Current Pharmaceutical Research, 2020)
Objective: The aim of this study was to analyze the phytoconstituents, estimation of total phenolic content and in vitro antioxidant activity of Zanthoxylum armatum from Myagdi district of Nepal. Methods: The seeds extract of Zanthoxylum armatum was prepared by cold percolation in hexane, ethyl acetate and methanol with continuous agitation. Phytochemical analysis for each extracts was performed by color differentiation method adopting the standard protocol. Antioxidant potential of the extracts was performed by DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenging assay by taking ascorbic acid as standard. Total phenolic content was estimated by Folin–Ciocalteu reagent method. Results: The analysis of secondary metabolites showed the presence of quinones and terpenoidsin almost all extracts while alkaloids, polyphenols, tannins and saponins were abundant in polar extracts. The results of antioxidant activity showed the methanol extract of Zanthoxylum armatum IC50 87.47µg/ml was found to be more antioxidant as compared to the standard ascorbic acid IC50 66.40 µg/ml. Ethyl acetate extract showed moderate antioxidant activity with IC50 142.04 µg/ml, whereas hexane extract showed the poor antioxidant activity with IC50 384.03 µg/ml. The result of total phenolic content showed, ethyl acetate fraction has the highest 26.28±9.35 mg GAE/g as compared to methanol extract 23.36±14.80 mg GAE/g and hexane extract showed the poor phenolic content 20.05±8.0 mg GAE/g. Conclusion: The seeds extracts of Zanthoxlum armatum were found the rich source of secondary metabolites. The methanol extract was found potent antioxidant as compared to ethyl acetate and hexane extract. It is concluded that further activity guided isolation approaches will be needed on methanol extract to identify the active compound responsible for in vivo and in vitro antioxidant activity.